Engaging Non-state Providers in Rural Water Supply Services : Documentation of Experiences in India - World Bank (New Delhi, 2014)
Taking an integrated approach to the country's rural water supply issues, Government of India's (GoI's) National Rural Drinking Water Program (NRDWP) focusses on the key aspects of source and system sustainability. System sustainability is inextricably linked to both technical and financial aspects of operations of rural water supply schemes. A key plank of NRDWP's approach as well as that of the sector reform project that preceded it is the devolution of Operations and Maintenance (O&M) functions, particularly related to distribution at the village level, to Gram Panchayats (GPs), or local government entities, through the formation of Village Water and Sanitation Committees (VWSCs). However, the lack of substantive community engagement in planning and implementation of schemes as well as capacity constraints in GPs has limited the spread and implementation of this approach. As reported in a recent study for the Planning Commission (PC, 2010), only a fourth of GPs surveyed reported VWSCs and less than one percent of the respondents were aware of the VWSCs' existence.